Transforming Environmental Policy through Adaptive Governance to Enhance Urban Socio-Ecological Resilience - Ahmed Mahdi Abdulkareem; Nirav Harshadbhai Shah; Dhruv Sanjaybhai (Adaptive Governance Research, 2025)
Purpose: This study examines the influence of adaptive governance on environmental policy transformation and its contribution to strengthening urban socio-ecological resilience in major metropolitan areas of India. The research seeks to explain how adaptive governance mechanisms support policy innovation and enhance the resilience of urban socio-ecological systems in response to increasingly complex environmental challenges. Subjects and Methods: A quantitative research design was employed using a cross-sectional survey conducted in 2024 involving 360 respondents from Delhi, Mumbai, and Chennai. Participants represented government institutions, environmental agencies, academics, urban planners, non-governmental organizations, and community leaders. Data were collected through structured questionnaires and analyzed using descriptive statistics, multiple linear regression, and Partial Least Squares Structural Equation Modeling (PLS-SEM). Instrument validity, reliability, and classical assumption tests were performed to ensure data quality. Results: The findings demonstrate that adaptive governance significantly promotes environmental policy transformation (β = 0.742; p < 0.001) and directly enhances urban socio-ecological resilience (β = 0.361; p < 0.001). Environmental policy transformation also exerts a significant positive influence on resilience (β = 0.412; p < 0.001). The structural model explains 64.8% of the variance in urban resilience, highlighting the importance of collaborative governance, institutional learning, and policy flexibility in improving adaptive capacity. Conclusions: Adaptive governance serves as a fundamental institutional driver of environmental policy transformation and urban socio-ecological resilience. Strengthening collaborative institutions, adaptive policy frameworks, and continuous organizational learning is essential for enhancing sustainable urban resilience under increasing environmental uncertainty.